Pemanfaatan Teknologi Informasi melalui Sistem Informasi Akademik Berbasis Web di SMP 2 Kudus - Setiyoadi, Amanda Diyas; Arifin, Muhammad (Lembaga Yasin AlSys, 2026)
Although digital transformation in education has been widely studied, research specifically focusing on the implementation of web-based Academic Information Systems (SIA) in resource-constrained secondary schools remains limited. This study aims to evaluate the effectiveness of a web-based SIA in improving the efficiency, accuracy, and transparency of academic administration at SMP 2 Kudus. A qualitative approach was employed using a participatory case study design, involving 15 participants including system operators, students, parents, and teachers. Data were collected through observation, interviews, and user surveys, and analyzed descriptively to assess system performance and user acceptance. The results indicate an 80 percent increase in administrative efficiency, a 90 percent reduction in data input errors, and a user satisfaction rate of 88 percent. These findings reinforce the relevance of the Technology Acceptance Model (TAM), which highlights perceived ease of use and perceived usefulness as key factors in technology adoption. The study concludes that successful digitalization in regional schools requires a participatory approach and user-centered system design. Its practical implications offer guidance for other schools seeking to sustainably adopt web-based academic information systems, while also contributing to the broader literature on digital transformation in basic education.